Hybrid biofunctional nanostructures as stimuli-responsive catalytic systems - Marten, Gernot U.; Gelbrich, Thorsten; Schmidt, Annette M. (Beilstein Journal of Organic Chemistry, 2010)
A novel active biocatalytic reaction system is proposed by covalently immobilizing porcine pancreas trypsin within the thermoresponsive polymer shell of superparamagnetic Fe3O4 nanoparticles.Active ester-functional nanocarriers suitable for the immobilization of amino functional targets are obtained in a single polymerization step by grafting-from copolymerization of an active ester monomer from superparamagnetic cores. The comonomer, oligo(ethylene glycol) methyl ether methacrylate, has excellent water solubility at room temperature, biocompatibility, and a tunable lower critical solution temperature (LCST) in water. The phase separation can alternatively be initiated by magnetic heating caused by magnetic losses in ac magnetic fields.The immobilization of porcine pancreas trypsin to the core–shell nanoparticles results in highly active, nanoparticulate biocatalysts that can easily be separated magnetically. The enzymatic activity of the obtained biocatalyst system can be influenced by outer stimuli, such as temperature and external magnetic fields, by utilizing the LCST of the copolymer shell.
Keywords: biocatalysis; biolabelling; core–shell nanoparticles; immobilization matrix; thermoflocculation